Swarna has a bag of cherries, and eats 2 1 of them, then passes the rest to Madhur, who eats 3 1 of the remainder. The bag is then passed to Bala, who eats 4 1 of the remaining cherries.
There are 6 cherries left. How many were there originally?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I ate only 4 cherries out of 24? Impossible!
Let x be the original number of cherries. Swarna eats 2 1 of them, so the remainder is x − 2 1 x = 2 1 x . Madhur eats 3 1 of the remainder, so the remainder is 2 1 x − 3 1 ( 2 1 x ) = 3 1 x . Bala eats 4 1 of the remaining cherries and 6 cherries were left. So, 3 1 x − 4 1 ( 3 1 x ) = 4 1 x = 6 . Hence, x = 4 × 6 = 2 4
assume number initially be 12, (LCM of 2, 3, 4)
Swarna ate 12/2 = 6 then remaining = 6
Madhur ate 6/3 = 2 remaining = 4
Bala ate 4/4 = 1 remaining = 3
when 3 cherries remaining, initially it was 12
so when 6 cherries remaining, initially it was 12/3 × 6 = 24
6 ÷ 4 3 ÷ 3 2 ÷ 2 1 = 2 4
If 6 cherries are left after eating 1/4, that means 24 were there originally. If 24 cherries were left after eating 1/3, that means that there were 72 originally. If 72 cherries were left after eating 1/2, then initially there must have been 144 cherries. Why are we saying that there were only 24 cherries originally?
Log in to reply
Only 1/4 were eaten, meaning that 6 cherries is 3/4 of what was there before 1/4 was eaten.
Problem Loading...
Note Loading...
Set Loading...
Let c be the number of cherries in the bag. If Swarna eats half of the cherries, then the remainder is c − 2 1 c . If Madhur eats 3 1 of that, then the remainder is ( c − 2 1 c ) − 3 1 ( c − 2 1 c ) . If Bala eats 4 1 of THAT, then the remainder is [ ( c − 2 1 c ) − 3 1 ( c − 2 1 c ) ] − 4 1 [ ( c − 2 1 c ) − 3 1 ( c − 2 1 c ) ] .
Since there are 6 cherries remaining, it can be said that [ ( c − 2 1 c ) − 3 1 ( c − 2 1 c ) ] − 4 1 [ ( c − 2 1 c ) − 3 1 ( c − 2 1 c ) ] = 6 , which when simplified gives c = 2 4 .
Lots of algebra!